The diversity and regional conservation status of wild edible fruit species in Sumatra, Indonesia - ADI BEJO SUWARDI; SYAMSUARDI SYAMSUARDI; ERIZAL MUKHTAR; NURAINAS NURAINAS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suwardi AB, Syamsuardi, Mukhtar E, Nurainas. 2023. The diversity and regional conservation status of wild edible fruit species in Sumatra, Indonesia. Biodiversitas 24: 3245-3257. Sumatra Island is recognized as the distribution center of tropical fruit species in Indonesia. However, increased human activity threatens the existence of edible wild fruit plants in nature. The study aims to assess the diversity and regional conservation status of wild edible fruit plant species in Sumatra, Indonesia. The study was conducted in four provinces: West Sumatra, Riau, Jambi, and Bengkulu. For the sampling, a modified line transect method was used. A total of 331 wild edible fruit plant species at four studied sites in Sumatra consisted of 73 families. The highest number of fruit plant species was recorded in West Sumatra Province, i.e., 176 species, followed by Jambi (172 species), Riau (121 species), and Bengkulu (76 species). The diversity of wild edible fruit plant species was higher in West Sumatra Province (3.85) but lower in Riau Province (3.25). Artocarpus integer (Thunb.) Merr., Baccaurea lanceolata (Miq.) Müll.Arg., Baccaurea macrocarpa (Miq.) Müll.Arg., Baccaurea polyneura Hook.f., Garcinia atroviridis Griff. ex T.Anderson, Garcinia xanthochymus Hook.fil. ex J.Anderson, Mangifera foetida Lour., Mangifera laurina Blume, Mangifera odorata Griff., and Pometia pinnata J.R.Forst. & G.Forst. were the most frequently recorded wild fruit plant species in all of the study area. However, 74 wild edible fruit plant species were recorded only in West Sumatra, 45 in Riau, 79 in Jambi, and 9 in Bengkulu. Among the 331 wild edible fruit species in the present study, 1 taxon was classified as endangered (0.30%), 9 taxa (2.72%) as vulnerable, 11 taxa (3.32%) as near threatened, and 139 taxa (41.99%) as least concern, and 171 taxa (51.67%) as Data Deficient.